Addition of PromOat Beta-Glucan and Guar-gum to Gluten- Free Wheat Starch Pan Bread to increase Fiber while maintaining the Quality in Texture - Singh,Devika (2023)
Gluten-free products have gained great attention in the last few years due to the growing incidence of celiac disease and the intolerance to gluten. The project is aimed to investigate the effects of adding PromOat, a good source of B-glucan to increase the fiber content and Guar-Gum to overcome the textural deformities in the gluten-free wheat starch Pan bread. Different levels of beta-glucan and guar-gum were divided into three treatments and the analysis of the moisture content, volume and water activity was done on the bread. The data was analyzed using the MATLAB in which ANOVA was implemented to check the statistical difference between the groups. There were differences in the moisture content values between the three treatments, especially in the third treatment which had both beta-glucan and guar-gum around 1% and 0.5% respectively. Differences were also seen in the water activity of the bread when guar gum was added. All the results that were obtained were summarized by the Principal Component Analysis (PCA), where it showed that moisture content was closely associated with guar-gum, beta-glucan and treatment. It was also concluded that the addition of the guar-gum doesn't have much influence on the volume of the bread.
Keywords: Gluten-Free bread; PromOat; Guar-Gum; Food technology